DNA adduct formation from the mutagenic air pollutant 3-nitrobenzanthrone - Bieler, Christian; Wießler, Manfred; Erdinger, Lothar; Suzuki, Hitomi; Enya, Takeji; Schmeiser, Heinz (Mutation research. Genetic toxicology and environmental mutagenesis, 1999)
The environmental contaminant 3-nitrobenzanthrone (3-nitro-7H-benz[d,e]anthracen-7-one) was recently shown to be a very strong bacterial mutagen, suggesting a new class of mutagenic compounds present in airborne particulate matter and diesel exhaust. Using the 32P-postlabeling assay, we investigated the capacity for 3-nitrobenzanthrone to form DNA adducts in vitro. Calf thymus DNA was incubated with 3-nitrobenzanthrone and either xanthine oxidase, a mammalian nitroreductase or rat liver S9 or zinc. Under these conditions 3-nitrobenzanthrone formed a total of seven adducts detectable by 32P-postlabeling. Using enrichment by butanol extraction the highest level of DNA adduct formation was found with activation by zinc (RAL: 88.4±32 per 108 nucleotides) followed by activation with xanthine oxidase (RAL: 75.5±12) and activation by rat liver S9 (RAL: 48.6±8). Three of the seven adduct spots were detected in all activation systems, however different amounts of individual spots were obtained in the different in vitro systems. The adduct pattern observed for the enzymatic incubations consisted of three major spots and was essentially identical. Chemical reduction of 3-nitrobenzanthrone by zinc resulted in five adduct spots whose formation was found to be concentration dependent. All adducts of 3-nitrobenzanthrone observed in this study migrated primarily along a diagonal zone, typical for DNA adducts derived from extracts of airborne particulate matter. When butanol enrichment was compared with nuclease P1 enrichment one adduct was clearly sensitive to the 3′-monophosphatase activity of nuclease P1. Our results demonstrate that 3-nitrobenzanthrone binds covalently to DNA after metabolic activation, forming multiple DNA adducts in vitro all of which are reduction products. These adducts may contribute to the known genotoxicity and carcinogenicity of extracts from airborne particulates.